I am action : literary and combat articles, thoughts, and revolutionary chronicles - Guerrero, Práxedis G., 1882-1910; Sethness-Castro, Javier (Chico, CA ; Edinburgh, Scotland : AK Press, 2018)
"Born into a wealthy family in Guanajuato, Mexico, in 1882, there was little indication that Praxedis G. Guerrero would evolve into a celebrated revolutionary. After a short stint in the military, from 1904-1910 he lived in the US, primarily in Colorado, California, and Texas. Journalist, poet, and above all, revolutionary, Guerrero lwas killed during the Mexican Revolution in 1910. This collection is comprised of his writings from the newspapers Revolucíon, Punto Rojo, and Regeneracíon, many appearing for the first time in English. Editor/translator Javier Sethness-Castro provides a biographical introduction and annotations of the pieces"--Provided by publisher.
"Praxedis G. Guerrero was born into a wealthy family in Guanajuato, Mexico, in 1882. While still a young man, he renounced his inheritance, claiming that he would rather earn his meals through manual labor than secure them by exploiting his fellow human being. Within less than a decade, he was a central figure in the transnational revolutionary network established by the Organizational Council of the Mexican Liberal Party (PLM), which was dedicated to deposing the dictator Porfirio Díaz and promoting anarchist revolution throughout Mexico. Guerrero was killed in battle at the age of twenty-eight in 1910. Guerrero was also one of the most prolific and talented revolutionary writers of his era, penning numerous articles that were known for both their literary style and their polemical force. In this volume, editor and translator Javier Sethness-Castro has collected a wide range of Guerrero's work for the newspapers Revolución, Punto Rojo, and Regeneración, most of them appearing for the first time in English. This edition also includes a biographical introduction and annotations for historical context throughout"--Print version, Page 4 of cover.
Program of the Pan-American Labor LeagueThe Probable Intervention; A Friend's Advice; The Means and the End; Women; Whites, Whites; Part II: Thoughts; Thoughts; He is Not Proletarian; He is Bourgeois; Revolutionary Women; Flash Points; Part III: Revolutionary Chronicles; Las Vacas; Viesca; Palomas; The Death of the Heroes; Part IV: Magón's Reminisces; Praxedis G. Guerrero Has Died; Praxedis G. Guerrero; A Letter from Ricardo Flores Magón; The Apostle; A Catastrophe; Copyright; Friends of AK Press
Includes bibliographical references.
In English, translated from Spanish.
Online resource; title from digital title page (viewed on September 10, 2018).
eBooks on EBSCOhost
Keywords: Guerrero, Práxedis G., -- 1882-1910 -- Translations into English; Partido Liberal Mexicano; Guerrero, Práxedis G., -- 1882-1910; Partido Liberal Mexicano; Mexico -- Politics and government -- 1867-1910.; Mexico -- History -- Revolution, 1910-1920.; Anarchism -- Mexico -- History -- 19th century; Anarchists -- Mexico -- History -- 19th century; Martyrs -- Mexico -- 19th century; Mexique -- Politique et gouvernement -- 1867-1910.; Mexique -- Histoire -- 1910-1920 (Révolution); Anarchisme -- Mexique -- Histoire -- 19e siècle.; Anarchistes -- Mexique -- Histoire -- 19e siècle.; Martyrs -- Mexique -- 19e siècle.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- Latin America -- Mexico; Anarchism; Anarchists; Martyrs; Politics and government; Mexico; 1800-1920; History; Translations